Investigation the Relationship Between Spin Deformity and Foot Plantar Pressure - Asma Haider Abdul-Jabbar (Central Asian Journal of Medical and Natural Science, 2023)
Plantar decompression is the area of pressure that acts between the foot and the foot Support surface during daily motor activities. Information derived from ex. Manometers are important in gait and posture research for lower extremity diagnosis Problems, and this paper reviews the properties of plantar foot sensors as reported in the literature on In addition to the plantar pressure measurement systems applied to a variety of research problems. The strengths and limitations of current and older wireless systems are discussed A suitable plantar pressure system was proposed to measure the high-pressure distributions and to know the deformation of the spine through measurements of some angles of the body through the plantar pressure under the foot with high accuracy and reliability. The new system is based on high linear pressure sensors without deceleration. The results were three parts. The first part is a photographic analysis of the system, the second part is the results of the plantar pressure, and the third is a comparison between the results to show the effect of the position deviation on the plantar pressure of both the left foot and the right foot